Family Financial Management In The Bumirejo Community, Pringlangu Subdistrict, Pekalongan District - Hardianto, Dhiky; Nugraha, Danang Adi; Mediana, Visti; Ramadhanita, Winne Putri; Azzahra, Siti; Kurniati, Panca; Fajriyah, Nuniek Nizmah (Urecol Journal. Part B: Economics and Business, 2025)
Introduction: Economic uncertainty, which is increasing due to global changes and local conditions such as inflation, has a direct impact on family financial stability. The community of Bumirejo, Pringlangu Village, Pekalongan Regency, faces challenges in managing family finances to meet basic needs and cope with economic pressures. Effective and planned financial management is crucial to maintaining family well-being during these difficult times. In response to these issues, a community service activity was conducted aimed at enhancing the community's ability to manage family finances effectively during times of economic uncertainty through education, practical guidance, and easily understandable support. The community service activity was implemented using an educational approach that directly involved families. Results: After the education, participants demonstrated improved knowledge and skills in creating family financial budgets, prioritizing expenses based on needs, and understanding the importance of setting aside emergency funds. The conclusion is that education and training in family financial management during times of economic uncertainty have a positive impact on improving community financial literacy. Many families have begun tracking their expenses and are committed to reducing unnecessary consumption-based spending. Awareness of the importance of disciplined financial management has also increased, which is expected to strengthen family economic resilience in uncertain situations. Recommendations include the need for continued mentoring and monitoring programs to ensure consistent implementation of financial management practices.